ANALISIS PELAYANAN BIDANG FARMASI MENGGUNAKAN INDIKATOR LAYANAN BERBASIS WHO: TINJAUAN SISTEMATIS : Analysis of Pharmaceutical Services Using WHO-Based Service Indicators: A Systematic Review - Yusnita Julyarni Akri (Forind Press, 2023)
Pharmaceutical services in hospitals are an inseparable part of the hospital's health service system that is oriented towards patient service, the provision of quality and affordable pharmaceutical preparations, medical devices, and consumables for all levels of society including clinical pharmacy services. The purpose of this study is to systematically review the implementation of pharmaceutical services based on WHO indicators. The articles used were selected from the Google Scholar journal database published from January 2013 to December 2023. Keywords for the study included